molecular-oncology 2018
DOI: 10.35841/molecular-oncology.2.2.38-41
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tumor lysis syndrome in a giant neglected breast cancer.

Abstract: Tumor lysis syndrome (TLS) is an oncologic emergency that generally triggered by effective cytotoxic chemotherapy in a context of rapidly proliferating and chemo-sensitive tumor or in patients with massive tumor burden. TLS has been rarely described in patients with solid tumors, and it is even more uncommon to have spontaneous tumor lysis syndrome (STLS). To our knowledge, only three cases of STLS in metastatic breast cancer were reported in the literature. Herein, we present a new case of STLS in a 37-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Time-to-TLS is an important consideration for deciding when these patients need to be monitored. Our patient was in frank TLS just 6 days following the first infusion, but a wide range of timing has been described in case reports (2–33 days [18]). The timeframe in which TLS should be monitored for is made further unclear due to the delayed onset of response with immunotherapy, which may be months after treatment initiation.…”
Section: Discussionmentioning
confidence: 89%
“…Time-to-TLS is an important consideration for deciding when these patients need to be monitored. Our patient was in frank TLS just 6 days following the first infusion, but a wide range of timing has been described in case reports (2–33 days [18]). The timeframe in which TLS should be monitored for is made further unclear due to the delayed onset of response with immunotherapy, which may be months after treatment initiation.…”
Section: Discussionmentioning
confidence: 89%
“…Since then, there has been a total of only 133 cases of TLS in solid tumors, with 33 of them occurring spontaneously [5-7]. Of these, STLS occurred in four cases of breast cancer [6-9].…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent study shows significant increase in cases of TLS associated with solid tumors [4]. TLS occurs in essentially every tumor type, such that the tumor burden itself is likely the more important factor than the tissue origin or location [3][4][5][6][7]. High tumor burden has classically been defined via three concrete measurements: bulky disease (>10 cm), elevated LDH (>2x upper limit of normal), and elevated WBC (>25,000) [9].…”
Section: Discussionmentioning
confidence: 99%
“…RCC is the most common solid lesion of the kidney, and more than 40% of patients eventually die from this disease. Although the true incidence of TLS in RCC is difficult to assess, we postulate that TLS in RCC may be underdiagnosed and underreported [3][4][5][6][7]. Several studies showed that a substantial proportion of TLS cases presenting to the emergency department (ED) were not recognized as such.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation